Expert Validation: A Critical Phase in the Development of ARIPSA - Muhajir, Siti Nurdianti; Warliani, Resti; Aprianti, Sinta (STKIP Singkawang, 2024)
The study aims to create an evaluative examination for problem-solving skills that incorporates Augmented Reality (AR) technology as a means of enhancing 21st-century education, with a specific focus on the domain of physics education. The tool, referred to as ARIPSA (Augmented Reality Integrated on Problem Solving Assessment), has been developed utilising the Borg and Gall research and development methodology. This research encompasses various significant stages, including an analysis of educational needs, the design of applications, as well as the development, dissemination, and deployment of those applications. The process of validation involves the participation of individuals with expertise in physics and technology, who evaluate the application to ascertain its efficacy and dependability. Additionally, they assess the quality of the physics-related information offered within the application. The validation findings suggest that ARIPSA demonstrates appropriateness and efficacy in an educational setting, particularly in enhancing students' problem-solving abilities.